Empowering women to engage in commercial agriculture - Ambler, Kate; Jones, Kelly M.; O'Sullivan, Michael (American Economic Association, 2022)
Despite women's large contributions to agricultural production in developing countries, they are often excluded from market-facing activities. There is little evidence on how to increase their participation in commercial agriculture. We designed a private sector intervention to encourage male outgrowers in Uganda to transfer a sugarcane contract to their wife or to register a previously uncontracted block in her name. A randomized controlled trial indicates that given some encouragement, men are willing to transfer rights to their wives for cane blocks of significant quality and value. Increased cane ownership by women increased women's participation in cane management and marketing activities.